An Analogy-Based Model for Convective Heat Transfer Coefficient in Petroleum and Chemical Pipe - Yin, T.N.; Gong, J.; Wang, L.; Zhang, J.B. (Asian Journal of Chemistry, 2011)
Temperature is an important parameter for chemical reaction and the overall heat transfer coefficient is a key parameter for the temperature calculation in petroleum and chemical pipe. Driven by the radial temperature gradient, the heat flows out of the pipe continuously, but the engineers have long neglected its impact. In fact, the heat transfer in the boundary layer can never be ignored. By analogy between heat and momentum, a convective heat transfer coefficient model for petroleum and chemical pipe is established, based on which the overall heat transfer coefficient is calculated and analyzed. The results show that the convective heat transfer in the boundary layer has great influence on the overall heat transfer.